Another bipolar deep-sea anemone: new species of Iosactis (Actiniaria, Endomyaria) from Antarctica - Rodríguez, E. (Helgoland Marine Research, 2011)
A new species of deep-sea burrowing sea anemone is described and illustrated from Antarctica. Iosactis antarctica sp. nov. is characterised by easily deciduous tentacles with sphincters in the base, smooth column, endodermal marginal sphincter, same mesenteries proximally and distally, 24 perfect mesenteries regularly arranged, diffuse retractor musculature and basilar muscles well developed. Iosactis antarctica sp. nov. is the second species of the deep-sea abyssal genus Iosactis; it differs from I. vagabunda in internal anatomy, cnidae and geographic distribution. The description of I. antarctica sp. nov. provides the opportunity to revaluate the morphology of the proximal end of this genus.